A study of breastfeeding practices, SARS-CoV-2 and its antibodies in the breast milk of mothers confirmed with COVID-19 - Sicong Peng; Huaping Zhu; Lixia Yang; Li Cao; Xiaona Huang; Michelle Dynes; Anuradha Narayan; Jianbo Xia; Yang Chen; Pei Zhang; Hongyan Liu; Hua Li; et al. (Elsevier, 2020)
Summary: Background: The possibility of 2019 novel coronavirus disease (COVID-19) transmission to neonates through breast milk remains unverified. Methods: This paper presents the interim results of a longitudinal study being carried out in Hubei province. As of 1 April 2020, 24 mothers confirmed with COVID-19, 19 mothers suspected with COVID-19 but Polymerase chain reaction negative, and 21 mothers without COVID-19 and their neonates have been recruited. Telephone follow-up was conducted to collect information on breastfeeding practices. Forty-four breast milk samples were collected from 16 of the 24 mothers with confirmed COVID-19 for the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) ribonucleic acid (RNA) and antibodies (IgM and IgG) testing. Findings: The average mother-child separation time was 36•7 ± 21•1 days among mothers confirmed with COVID-19, significantly longer than that of the suspected group (16•6 ± 13•1 days) and control group (10•5 ± 8•2 days). Both the COVID-19 confirmed (58•3%) and suspected (52•6%) groups presented significantly lower rates of breastfeeding as compared with the control group (95•2%). All 44 breast milk samples tested negative for the SARS-CoV-2 nucleic acid. Thirty-eight breast milk samples underwent antibody testing and all tested negative for IgG. Twenty-one breast milk samples from 8 women tested positive for IgM, while the remaining samples from 11 women tested negative. Interpretation: Considering the lack of evidence for SARS-CoV-2 transmission through breast milk, breastfeeding counselling along with appropriate hand hygiene precautions and facemasks should be provided to all pregnant women. Funding: The study was funded by the Hong Kong Committee for UNICEF.